Nellix stent graft explant: a great challenge for late open conversion of failed endovascular aortic repair - Sousa, Pedro Pinto (2023)
INTRODUCTION: The concept of the Nellix endoprosthesis is based on endovascular aneurysm sealing with endobags and was launched in the market for endovascular abdominal aortic aneurysm repair (EVAR). The manufacturer recently issued a hazard alert due to higher rates of endoleaks, migration and aneurysm enlargement. CASE REPORT: The authors present a clinical case of a seventy year-old man previously submitted to EVAR with a Nellix device in another country. The patient presented with an asymptomatic Type Ia endoleak and proximal aortic neck aneurysmatic degeneration. The anatomy was considered unfavourable for further endovascular management. After multidisciplinary discussion and workup, open surgical conversion was selected. Complete endoprosthesis explantation and in-situ reconstruction were performed. The post-operative course was uneventful. CONCLUSION: Once presented with a patient considered fit for open surgical conversion and with aneurysm morphology unfavourable for endovascular, the authors believe that open conversion may constitute a very acceptable method of repair and should be offered.